DAMPAK WISATA PANTAI TEDIS TERHADAP PENDAPATAN UMKM KOTA KUPANG - Laka, Merlin; Lian, Yohanes P; Semi, Yohan; Danggur, Gio (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2024)
Tedis Beach tourism in Kupang City has great potential in increasing people's income, especially for Micro, Small and Medium Enterprises (MSMEs). However, the concrete impact of the existence of this tourism on MSME income. This research aims to analyze the impact of Tedis Beach tourism on MSME income in Kupang City, as well as identifying opportunities and challenges faced by MSME actors around the tourist area. This research uses a descriptive qualitative approach with data collection techniques through interviews, observation and documentation. Respondents consisted of MSME actors operating in the culinary sector around Tedis Beach. The research results showed that Tedis Beach tourism had a significant positive impact on MSME income, with an increase in daily income for business actors from IDR 100,000 – IDR 300,000 to IDR 400,000 – IDR 700,000 at the time. tourist visits increase. Business actors also reported increased satisfaction with the income earned. Tourism development at Tedis Beach contributes positively to local economic growth and community welfare. Support from the government and community participation are very important for the sustainabilityand development of MSMEs tourist areas.